Transformative learning theory, a theory in progress? Thoughts from a Habermasian perspective - Saskia Eschenbacher (Adult Education Research Conference, 2021)
Mezirow borrows heavily from Habermas utilizing core concepts of his theory. However, this activity has serious shortcomings. This paper explores these shortcomings and contributes to the further development of the theory of transformative learning (TL). This paper focuses on three philosophical aspects of transformation theory. I (1) underline inaccuracies and misunderstandings of Habermas' ideas utilized by Mezirow. It will (2) identify theoretical shortcomings and problems in the work of Habermas transposed onto Mezirow's theory of transformative learning. And (3) finally I argue for a way forward for the theory of transformative learning to become a theory in progress.
Keywords: Transformative learning theory; Habermas; Mezirow; theory development